Fulvic Acid Attenuates Atopic Dermatitis by Downregulating CCL17/22 - Chenxi Wu; Anqi Lyu; Shijun Shan (Molecules, 2023)
The main pathogenic factor in atopic dermatitis (AD) is Th2 inflammation, and levels of serum CCL17 and CCL22 are related to severity in AD patients. Fulvic acid (FA) is a kind of natural humic acid with anti-inflammatory, antibacterial, and immunomodulatory effects. Our experiments demonstrated the therapeutic effect of FA on AD mice and revealed some potential mechanisms. FA was shown to reduce TARC/CCL17 and MDC/CCL22 expression in HaCaT cells stimulated by TNF-α and IFN-γ. The inhibitors showed that FA inhibits CCL17 and CCL22 production by deactivating the p38 MAPK and JNK pathways. After 2,4-dinitrochlorobenzene (DNCB) induction in mice with atopic dermatitis, FA effectively reduced the symptoms and serum levels of CCL17 and CCL22. In conclusion, topical FA attenuated AD via downregulation of CCL17 and CCL22, via inhibition of P38 MAPK and JNK phosphorylation, and FA is a potential therapeutic agent for AD.